2009
DOI: 10.1002/pola.23311
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively linking fullerene and conjugated polymers

Abstract: The stereo-electronic control over bisadditions of conjugated polymers to fullerene (C 60 ) is explored in the formation of alternating copolymers. The chemistry, resulting configuration, and properties of poly(3-hexylthiophene)-alt-C 60 copolymers prepared by either classic pyrrolidine ring formation or an atom transfer radical addition are compared. Both routes result in controlled additions of polymers to C 60 . Extensive macromolecular modeling through PM6 methods indicate that there is no conjugation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 67 publications
3
40
0
Order By: Relevance
“…119 It was also noted elsewhere, as an intuitive argument, that placing insulating groups right next to the electrodes would considerably diminish charge transfer and that rather, a parallel placement of block copolymers with respect the electrodes might be more appropriate. 169 This would also enhance the particularly important polymer-electrode interactions.…”
Section: As Single and Multicomponent Layersmentioning
confidence: 99%
“…119 It was also noted elsewhere, as an intuitive argument, that placing insulating groups right next to the electrodes would considerably diminish charge transfer and that rather, a parallel placement of block copolymers with respect the electrodes might be more appropriate. 169 This would also enhance the particularly important polymer-electrode interactions.…”
Section: As Single and Multicomponent Layersmentioning
confidence: 99%
“…The self consistent field electronic structure was considered converged when the energy of two cycles changes by less than 10 -5 Hartree. The DFT/B3LYP/6-31G(1d) methodology has been widely employed in studies of conjugated polymers, where it has been shown to yield good results 14,16,28 . We analyzed the data for the lowest unoccupied and highest occupied molecular orbitals energy (LUMD and HDMD, respectively) and the energy gap between LUMD and HDMD (E g ).…”
Section: Calculation Proceduresmentioning
confidence: 99%
“…All studied structures were optimized by the HartreeFock semiempirical Parametric Method 6 (PM6) 26 implemented in the computational package MDPAC2012 27 . We chose PM6 because of its satisfactory performance in studies with polythiophene derivatives 8,9,16,28,29 . The geometry optimization process was considered completed when the gradient norm drops below 0.01 kcal.mol -1 /Å.…”
Section: Calculation Proceduresmentioning
confidence: 99%
“…The relationship between polymer M W and PCE has been exhaustively studied in 301 P3HT and mixtures with PCBM [49][50][51][52][53][54][55][56][57][58][59][60][61]. We will attempt to briefly summarize the 302 lessons here.…”
mentioning
confidence: 99%
“…In the OPV field, the drying time for a film was not purposefully controlled until 493 with PCBM has been studied in great detail [42,56,59,70,76,. Optimized 494 thermally annealed devices are spin-coated from a chlorobenzene solution in a ratio 495 that contains 35-45% PCBM by weight.…”
mentioning
confidence: 99%